The Gut Microbiota-Bile Acids-TGR5 Axis Mediates Eucommia ulmoides Leaf Extract Alleviation of Injury to Colonic Epithelium Integrity - Zhai, Zhenya; Niu, Kai-Min; Liu, Yichun; Lin, Chong; Wu, Xin (Frontiers in Microbiology, 2021)
Eucommia ulmoides leaves (EL) are rich in phenolic acids and flavonoids, showing enhancing intestinal health effects. The intestinal microbiota-bile acid axis plays important roles in the occurrence and recovery of inflammatory bowel disease (IBD). However, whether EL extract (ELE) has regulatory effects on the intestinal microbiota, bile acid metabolism and IBD is still unclear. To fill this gap, 2% dextran sulfate sodium (DSS) induced mild IBD in a C57BL/6J mouse model that was treated with 200 and 400 mg/kg (intake dose/body weight) ELE was used. Oral ELE supplementation alleviated DSS induced shortening of colon and colonic epithelial injury. Compared to the DSS group, ELE supplementation significantly decreased Toll-like receptor 4 (TLR4) and interlukin-6 (IL-6) amdincreased occludin and claudin-1 mRNA expression level in the colon (p<0.05). Combined 16S rRNA gene sequencing and targeted metabolomic analyses demonstrated that ELE significantly improved the diversity and richness of the intestinal microbiota, decreased the abundance of Bacteroidaceae, and increased Akkermansiaceae and Ruminococcaceae abundance (p<0.05) compared with DSS-induced IBD mice. Moreover, ELE significantly increased the serum contents of deoxycholic acid (DCA) and tauroursodeoxycholic acid (TUDCA), which were highly positively correlated with Akkermansia and unidentified_Ruminococccaceae relative to the DSS group. Then we found that ELE increased Takeda G-protein coupled receptor 5 (TGR5), claudin-1 and occludin mRNA expression levels in the colon. In the Caco-2 cell model, we confirmed that activation of TGR5 improved the reduction in transepithelial electoral resistance (TEER) and decreased the permeability of FITC-Dextran on monolayer cells induced by LPS (p<0.05). siRNA interference assays showed that the decrease in TGR5 expression led to the decrease in TEER, an increase in FITC-dextran permeability, and a decrease in claudin-1 protein expression in Caco-2 cells. In summary, ELE alleviated IBD by influencing the intestinal microbiota structure and composition of bile acids, which in turn activated the colonic TGR5 gene expression in the colon and promoted the expression of tight junction proteins. These findings provide new insight for using ELE as a functional food with adjuvant therapeutic effects in IBD.